PAHAM YESUS KRISTUS MENURUT ATHANASIUS DARI ALEKSANDRIA DALAM CONTRA GENTES – DE INCARNATIONE - Sendjaja, Hendri Mulyana (Jurnal Orientasi Baru, 2012)
In his double treatise, Contra Gentes and De Incarnatione, Athanasius proposes a Logos Christology from the soteriological perspective. According to him, Christ is the Logos of God, Father’s proper ‘offspring’, the only Father’s Begotten Son, the ‘Unchanging Image’ of the Father. Christ as the Logos of God does God’s works, both Creation, Providence and Salvation’s works. In His Salvation work, by the works indicated through His human body, Jesus Christ, the Incarnate Logos, does the God’s works, reveals God ‘who is good’, ‘who is the lover of humanity’, to human that fall into sin. Jesus surrenders His own body as an offering and a sacrifice for the sake of salvation of all creation.